Evaluation of Partial Discharge Measurement as a Non-Destructive Measurement Procedure for Ceramic Substrates - Drechsel, Johannes; Barth, Henry; Rebenklau, Lars (International spring seminar on electronics technology : ISSE, 2021)
Partial discharge measurements are typically used for non-destructive insulation tests of high voltage devices like generators, transformers, switchgear, and cabling. This work merges the corresponding knowledge present in literature and evaluates its applicability to ceramic substrates used in power electronics. For this purpose, a transient recorder-based measurement system is programmed, tested, and compared to a commercial system. The experimental setup is analyzed and adapted to the measurement method. Multiple algorithms are evaluated in regard to their suitability for partial discharge data analysis. First measurements hypothesize correlations between defects in the substrate and its partial discharge characteristics.